2012
DOI: 10.4103/0973-1482.98974
|View full text |Cite
|
Sign up to set email alerts
|

Participation in decision making regarding type of surgery and treatment-related satisfaction in North Indian women with early breast cancer

Abstract: North Indian women do not independently take decision regarding any type of surgery. The reason for opting for either kind of surgery was based on surgeon's recommendation or concern about recurrence. Body image was not an issue amongst majority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(59 citation statements)
references
References 13 publications
(16 reference statements)
0
59
0
Order By: Relevance
“…All 32 included publications had a cross‐sectional study design, 11 of which derived their patient population from previous cohort studies, or from the control group of a randomized trial. Twenty of the 32 studies were published after 2010, 11 between 2000 and 2010, and one in 1989.…”
Section: Resultsmentioning
confidence: 99%
“…All 32 included publications had a cross‐sectional study design, 11 of which derived their patient population from previous cohort studies, or from the control group of a randomized trial. Twenty of the 32 studies were published after 2010, 11 between 2000 and 2010, and one in 1989.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies have also shown that there is a need to maintain a balance about the provision of right amount and type of information [11]. In the Indian context, as reported in another study as well, patients tend to leave the choice of treatment with the treating team [12]. In such situations, a counsellor/breast navigator can play an effective role in handling the informational and emotional needs of the patients and the family thereby, reducing time-related pressure on the treating team [13,14].…”
Section: Discussionmentioning
confidence: 96%
“…They say, BIf the doctor says, I have to do this, I have to do this…B they don't even question… He's God… that faith cures people more than other stuff but yet if you see amongst the general populace especially the urban, without counselling, they're suffering a huge lot.^ (12).…”
Section: Cultural Normsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that 35% of Turkish surgeons let their patients choose the technique (BCS or mastectomy) after informing them, whereas the rest tend to direct their patients towards the choice they believe to be most appropriate [7]. When choosing between BCS or mastectomy, independent decision-making rates are over 50% in Western countries compared to as low as 10% in countries like India [8]. The striking outcome of these population-based studies is that in countries where literacy and employment rates are low, patients tend to be excluded from the decision-making process about their surgery.…”
Section: Resultsmentioning
confidence: 99%